Ensayo comparativo de híbridos y variedades tropicales de maíz (Zea mays L) en Zungaro cocha. San Juan. 2022 - Velasquez Flores, Gonzalo Alejandro (2025)
The objective of the research was to study the behavior in agronomic characteristics and yield components among nine corn genotypes (6 varieties and three hybrids). Due to its approach, it was quantitative, prospective, explanatory level and experimental research design. The target population was 2,304 corn plants, distributed at a rate of 64 plants / genotype from which samples of 28 plants were taken for each genotype, making a total of 1,008 hard yellow corn plants belonging to the El Porvenir experimental station in Tarapoto. The experimental design was a Randomized Complete Block Design (DBCA) with four replications. The data obtained were analyzed through the R software and its graphical interface R Studio version 4.4.1. Graphical tests of homogeneity of variances, normality, independence and additivity were performed. Among the main conclusions obtained were that the hybrids of yellow hard corn, particularly Hybrid 1 and Hta4, demonstrated significant statistical superiority in grain yield. Although some varieties such as Marginal 28T and Nutrimaiz showed competitive values in specific morphological components (length and diameter of cob), this did not translate into higher grain yields, confirming that the final yield is more influenced by the joint effect of multiple components than by characteristics, recommending to prioritize the sowing of Hybrid 1 and Hta4 when the main objective is to maximize grain yield per hectare, but which must also consider economic aspects such as the cost of hybrid seed versus variety seed, as well as the possibility of reusing seeds in the case of varieties.